Globalization and Identity: Some Remarks on the Modes of Lithuanian Identity Discourse - Donskis, Leonidas (Sociologija. Mintis ir veiksmas, 2006)
Contemporary society’s human identity is multidimensional and pierces at least several layers of cultural and social experience. Vytautas Kavolis analyzed postmodern identity as an attempt to bridge what was cleaved off by modernity, joining modernism and antimodernism in our consciousness and culture. Does it make sense to return, at the beginning of the twenty-first century, to some worn-out models of self comprehension and identity describing loyalty as a sort of uncompromising battle for, and defence of, the nation and its history? Or should we rely, instead, on our ability to fill the gaps bridging ourselves and the others in terms of open-mindedness, understanding, and devotion to our culture combined with responsiveness to other cultures? Can we inherit identity in an age when it tends to be a matter of conscious choice and achievement, rather than ascription? The article addresses all these issues describing identity in the age of globalization as a symbolic design within which we search for the concepts and the frames of meaning to interpret ourselves and the world around us.
Keywords: identity; globalization; modernity